Helicobacter pylori infection in humans and phytotherapy, probiotics, and emerging therapeutic interventions: a review - Liu, Mengkai; Gao, Hui; Miao, Jinlai; Zhang, Ziyan; Zheng, Lili; Li, Fei; Zhou, Sen; Zhang, Zhiran; Li, Shengxin; Liu, He; Sun, Jie (Frontiers in Microbiology, 2024)
The global prevalence of Helicobacter pylori (H. pylori) infection remains high, indicating a persistent presence of this pathogenic bacterium capable of infecting humans. This review summarizes the population demographics, transmission routes, as well as conventional and novel therapeutic approaches for H. pylori infection. The prevalence of H. pylori infection exceeds 30% in numerous countries worldwide and can be transmitted through interpersonal and zoonotic routes. Cytotoxin-related gene A(CagA) and vacuolar cytotoxin A(VacA) are the main virulence factors of H. pylori, contributing to its steep global infection rate. Preventative measures should be taken from people's living habits and dietary factors to reduce H. pylori infection. Plant therapies, probiotics therapies and some emerging therapies have emerged as alternative treatments for H. pylori infection, addressing the issue of elevated antibiotic resistance rates. Plant extracts primarily target urease activity and adhesion activity to treat H. pylori, while probiotics prevent H. pylori infection through both immune and non-immune pathways. In the future, the primary research focus will be on combining multiple treatment methods to effectively eradicate H. pylori infection.